Dialektika Teologi dari Perspektif Herman Bavinck dengan Pemikiran Ekonomi Marxisme - Rinto Pangaribuan (Indonesian Journal of Theology, 2022)
The position of a Weberian social theory strongly correlates capitalism with Calvinism. As such, one might expect Reformed (Calvinist) theology to stand in principled opposition to Marxist ideology. Using comparative literary method, this study assesses such a Weberian thesis by placing Calvinism and Marxism in dialectical relation. Modeling a Calvinistic theological perspective, the intellectual and political oeuvre of Herman Bavinck presents an ostensible rejection of Marxism. Meanwhile, this paper also considers the analytical tradition represented by Karl Marx, whose thinking centers economic productivity amid a radical reading of human history. Presenting a theoretical contrast, Bavinck grounds his theological method on revelation, while Marx relies on the material conditions of economic activity to scaffold his philosophical thought. Despite considerable methodological and epistemological differences, however, the theoretical groundings and approaches of both Bavinck and Marx may comprise a point of synthesis within the realm of practical action, or praxis. In doing so, Bavinck’s Reformed commitments can frame an orientation to Marxian emancipatory praxis, whereas Marx’s critical theorization can offer practical concreteness to a Bavinckian theology. A collaborative-complementary resolution to the apparent ideological contradiction is, therefore, put forward on the basis of praxis.